Novel battery thermal management system for electric vehicles with a loop heat pipe and graphite sheet inserts. (25th July 2021) - Bernagozzi, Marco; Georgoulas, Anastasios; Miché, Nicolas; Rouaud, Cedric; Marengo, Marco
Highlights: New battery thermal management proposed with Loop Heat Pipes and graphite sheets. Loop Heat Pipe is a passive technology so no need for parasitic power or maintenance. Feasibility verified through numerical model validated by experimental demonstrator. Proposed design reduces maximum temperature by 3.6 °C compared to liquid cold plate. Numerical model proved useful as design tool for working fluid and materials. Abstract: Aiming to improve on key Electric Vehicles issues, such as maximum temperature during fast charging, parasitic power and cost reduction, an innovative thermal management system for a 3-cell battery module, including a flat plate Loop Heat Pipe and graphite sheet inserts, is presented. The proposed Loop Heat Pipe, located at the bottom of the module, can transfer efficiently up to 150 W from the battery module to a remote heat exchanger connected to the HVAC chiller of the vehicle. Graphite sheets have the twofold function of promoting heat transfer along the cell plane direction, while hindering it in the transverse direction. Since Loop Heat Pipes need no electrical power, this design allows for a reduction of parasitic power consumption, as well as a reduction in the need of maintenance, with respect to standard forced air or liquid-based thermal management systems. The design feasibility was verified thanks to a Lumped Parameter Model, which was validated against in-house experimental data, using a copper/copper flat plate Loop Heat Pipe and two different working fluids, ethanol and water. Results showed that this design complies with the battery thermal requirements both at pack and cell level, with maximum temperature during fast charge and temperature spread across the cell being 31.5 °C and 2 °C, respectively, during ambient temperature tests. When compared against a liquid cold plate design, this new design lowered the maximum temperature after fast charge by 3.6 °C. Finally, the developed model proved able to predict the effects of design parameters on the thermal performance of the system.